Heartstopper, volume 5 ebook - Oseman, Alice (Heartstopper, 2023)
*Now an acclaimed live-action Netflix series!* Boy meets boy. Boys become friends. Boys fall in love. The bestselling LGBTQ+ graphic novel about life, love, and everything that happens in between: this is the fifth volume of the much-loved HEARTSTOPPER series, featuring gorgeous two-color artwork. Nick and Charlie are in love. They've finally said those three little words, and Charlie has almost persuaded his mum to let him sleep over at Nick's house. He wants to take their relationship to the next level... but can he find the confidence he needs? And with Nick going off to university next year, is everything about to change? By Alice Oseman, winner of the YA Book Prize, Heartstopper encompasses all the small moments of Nick and Charlie's lives that together make up something larger, which speaks to all of us. Contains discussions around mental health and eating disorders, and sexual references.